STUDY OF CLIMATIC DROUGHT STATUS IN QUANG TRI PROVINCE - Tuan, Doan Doan; Hoang, Nguyen Van; Loi, Nguyen Van (Vietnam Journal of Earth Sciences, 2014)
Quang Tri province is an area where drought rather often occurs, and severely occurred in many years. Climatic drought had been studied and analyzed based on 28-year data in the period 1985-2012. Monthly dry-wet status of this period had been compiled and presented in distribution graphs. The interpretation and analysis have shown that the drought frequency situation in the province is as follows: 7.87 drought week per year, 0.66 drought week per month (in average two drought weeks per 3 months); 3 drought period per year; drought month frequency is: (1) 13.8% for dry months; (2) 12.1% for wet months; (3) 12.2% for all seasonal months; drought season (dry or wet season) almost only ccurs in dry seasons (excepts 2006 was drought year) with frequency 17.9% (about 5.6 years one time). Drought months determined by accumulative rainfall criteria and drought coefficient have given higher frequency in compare to other drought criteria. Quang Tri has almost every year drought weeks and drought period, approximately during 8.2 years there is one year with drought month, and during 5.6 years there is one year with drought season.ReferencesNguyễn Duy Chinh (chủ biên), 2002. Đánh giá đặc điểm khí hậu tỉnh Quảng Trị. Đề tài nhánh thuộc đề tài “Xây dựng cơ sở dữ liệu và đánh giá đặc điểm khí tượng thủy văn phục vụ phát triển kinh tế - xã hội tỉnh Quảng Trị”. UBND tỉnh Quảng Trị.Nguyễn Trọng Hiệu, 1998. Phân bố hạn và tác động của chúng ở miền Trung. Báo cáo kết quả đề tài nghiên cứu khoa học Tổng cục Khí tượng Thủy văn (từ tháng 8/2002 là Trung tâm Khí tượng Thuỷ văn Quốc gia - Bộ TNMT; từ tháng 3/2013 là Cục Khí tượng Thủy văn và Biến đổi Khí hậu - Bộ TNMT).Nguyễn Thị Nga, Nguyễn Phương Nhung, 2009. Tài nguyên nước mặt tỉnh Quảng Trị. Tạp chí Khoa học ĐHQGHN-Khoa học Tự nhiên và Công nghệ 25, Số 3S. Trang 472‐483.Nguyễn Thám, Nguyễn Hoàng Sơn, 2011. Đánh giá tài nguyên sinh thái khí hậu phục vụ phát triển du lịch tỉnh Quảng Trị. Tạp chí Khoa học Đại học Huế, số 65.Ban chỉ huy PCLB & TKCN tỉnh Quảng Trị UBND tỉnh Quảng Trị, 2011. Báo cáo tổng kết công tác PCLB & Giảm nhẹ thiên tai 1998 - 2010.Trung tâm Dự báo Khí tượng Thủy văn Trung ương-Bộ Tài nguyên và Môi trường. Dữ liệu khí tượng thủy văn Quảng Trị 1985-2012.